2000
DOI: 10.3168/jds.s0022-0302(00)75185-x
|View full text |Cite
|
Sign up to set email alerts
|

Corn Silage Hybrid Effects on Intake, Digestion, and Milk Production by Dairy Cows

Abstract: Three corn hybrids harvested as whole-plant silage were evaluated in three separate feeding trials with lactating dairy cows. In trial 1, 24 multiparous Holstein cows were used in a replicated 4 x 4 Latin square with 28-d periods. Treatments were conventional (Pioneer 3563) and leafy (Mycogen TMF 106) corn silage hybrids, each planted at low (59,000 plants/ha) and high (79,000 plants/ha) plant populations. There were no milk production differences between treatments. Total-tract digestibility of dietary starch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 22 publications
2
45
0
2
Order By: Relevance
“…However, in their study, the passage rate for the brown midrib diet was also faster so that the increased rate of passage could have negated any increase in rumen digestibility. Other studies have also shown no difference in total-tract OM digestibility of a high-NDF digestibility and a lower NDF digestibility silage (Kuehn et al, 1999;Oba and Allen, 1999b;Bal et al, 2000). One possible explanation for the increase in ruminal turnover without an increase in total-tract OM digestibility is that the increased digestibility of the NDF in the rumen accounted for much of the increase in OM turnover in the rumen, but postruminally the OM that was passed out of the rumen was digested similarly between the 2 diets.…”
Section: Trial 1 -Forage Substitution On a Dm Basismentioning
confidence: 90%
“…However, in their study, the passage rate for the brown midrib diet was also faster so that the increased rate of passage could have negated any increase in rumen digestibility. Other studies have also shown no difference in total-tract OM digestibility of a high-NDF digestibility and a lower NDF digestibility silage (Kuehn et al, 1999;Oba and Allen, 1999b;Bal et al, 2000). One possible explanation for the increase in ruminal turnover without an increase in total-tract OM digestibility is that the increased digestibility of the NDF in the rumen accounted for much of the increase in OM turnover in the rumen, but postruminally the OM that was passed out of the rumen was digested similarly between the 2 diets.…”
Section: Trial 1 -Forage Substitution On a Dm Basismentioning
confidence: 90%
“…The milk composition was calculated as the average of the triple samples, using the portion of daily production at milking time as a weighting factor (Bal et al, 2000). Acid detergent insoluble ash (ADIA) concentration was measured in the composited diet and faecal samples, and used as an internal marker to calculate the apparent total-tract digestibility of the nutrients (Nikkhah et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…Recent unpublished data of Inra Lusignan showed that organic matter digestibility measured on wethers in digestibility crates ranged from 65.3 to 74.4% in a set of 232 registered early maize hybrids (mean value was 69.9%), and reached 76.8% in bm3 hybrids. Genetic variation in maize silage efficiency for milk or meat yield and quality was also proved in comparison (i) between normal hybrids [1,7,20], (ii) between normal and bm3 hybrids [4,5,17,26] and (iii) between normal and leafy hybrids [10,22,25] despite the fact that in these last experiments normal and leafy hybrids were not isogenic, and therefore the higher milk yield could not definitely be related to the leafy trait. Efficient methods are available for breeding maize of higher whole plant and cell wall digestibility.…”
Section: Introductionmentioning
confidence: 99%
“…Cows were paired and Maize silage ingestibility 491 4 hybrids out of the 6 tested hybrids, during 4 periods. For each hybrid and each set of cows, measurements were performed for 10 days over 2 weeks, after 2 weeks of pre-experimental feeding with the involved hybrid.…”
Section: Dairy Cattle Experimentsmentioning
confidence: 99%